Comparison of The Effectiveness of Gel and Spray Hand Sanitizers Against Reducing The Number of Germs on The Palms - Pipin Supenah; Usdiyanto Usdiyanto; Misika Misika (Riviera Publishing, 2022)
Maintaining hand hygiene is one of the measures recommended by the Centers for Disease Control and Prevention (CDC) to help prevent infection during the COVID-19 pandemic. Maintaining hand hygiene can use soap and water or other alternatives such as hand sanitizer with an alcohol content of at least 60%. Hand sanitizer is a hand sanitizer that contains alcohol functions to kill microorganisms in the hands quickly and without rinsing. Hand sanitizers generally consist of two types, namely gels and sprays, both of which have their own advantages and disadvantages. This study aimed to determine the decrease in the number of germs on the palms after using gel and spray hand sanitizers, as well as a comparison of the effectiveness of gel and spray hand sanitizers. The research method used is pre-experimental with the research design